AB0052 Toll-Like Receptor 4-Induced Interleukin-1 Defines the Intestinal Microbiome and Mucosal Immune Response in Arthritis-Prone IL-1 Receptor Antagonist Deficient Mice. (9th June 2015) - Abdollahi-Roodsaz, S.; Ederveen, T.; Rogier, R.; Boekhorst, J.; Wopereis, H.; Garssen, J.; van de Loo, F.; Koenders, M.; van Hijum, S.; van den Berg, W.
Abstract : Background: Mice deficient in interleukin-1 receptor antagonist (IL-1Ra -/- ) spontaneously develop a T cell-driven autoimmune arthritis, which we previously showed to depend on the presence of commensal microbiota. Recent findings suggest alteration of intestinal microbiome in new-onset rheumatoid arthritis (RA). Objectives: The aim of this study was to investigate the role of IL-1 receptor signaling and Toll-like receptor (TLR) 2 and TLR4 in defining the intestinal microbiota and the associated mucosal and systemic immune response during arthritis. Methods: Multiplex 454 pyrosequencing of fecal bacterial 16S rRNA was used to define intestinal microbial communities in BALB/c wild type (WT), IL-1Ra -/- and IL-1Ra/TLR double knock-out (DKO) mice. For gene sequencing analysis, a customized workflow based on Quantitative Insights Into Microbial Ecology (QIIME version 1.2) was adopted. T cell differentiation was assessed in small intestine lamina propria (SI-LP) and spleen using flow cytometry and gene expression was assessed by qPCR. Results: IL-1Ra -/- mice had a significant reduction in microbial diversity compared to WT mice. Both alpha diversity (number of unique taxonomic entities) and phylogenetic diversity (PD) whole tree (based on taxonomic distance) were significantly diminished in IL-1Ra -/- mice. Interestingly, the loss of species diversity was absent in IL-1Ra/TLR4 DKO, but not IL-1Ra/TLR2 DKO mice, suggesting that IL-1R-driven skewing of bacterial diversity depends on TLR4. IL-1Ra -/- mice exhibited significantly increased abundance of the genus Helicobacter and reduced Prevotella ( p =0.008 and p =0.004, respectively). Importantly, significant alterations in the genera Xylanibacter, Prevotella, Streptococcus, and Ruminococcus were markedly normalized in TLR4, but not TLR2, deficient mice, identifying a role for TLR4 in IL-1 mediated shifts in microbial community. In line with the relevance of intestinal microbiota in mucosal T cell polarization, IL-1Ra -/- mice had greatly increased Th17 in SI-LP. Interestingly, SI-LP Th17% significantly correlated with arthritis score. Although intestinal mRNA expression of IL-1 itself remained unaltered, IL-23p19 expression was increased. Both IL-1b and IL-23 were significantly diminished in IL-1Ra/TLR4 DKO mice, suggesting a TLR4-mediated regulation. These mucosal responses paralleled systemic response and arthritis development, since Th17% and associated genes such as RORγt were increased in IL-1Ra -/- and reduced in IL-1Ra/TLR4 DKO mice which had less severe arthritis. Conclusions: These data suggest a TLR4-mediated regulation of intestinal microbiome, and mucosal and splenic immune responses controlling arthritis severity, potentially through an IL-1 and IL-23 dependent mechanism. Understanding the molecular and cellular mechanisms linking the intestinal T cell response with arthritis may help identifying novel therapeutic targets in RA. Disclosure of Interest: None declared